2009
DOI: 10.1542/peds.2008-1578g
|View full text |Cite
|
Sign up to set email alerts
|

Report of Colloquium III: Challenges for Pediatric Graduate Medical Education and How to Meet Them—A Quality Improvement Approach to Innovation in Pediatric Graduate Medical Education

Abstract: Participants of the third colloquium of the Residency Review and Redesign in Pediatrics (R 3 P) Project concluded that pediatricians who practice ambulatory, hospital-based, a combination of ambulatory and hospital-based, and subspecialty pediatrics are sufficiently different to justify differences in general pediatric residency training. This conclusion along with others of previous colloquia led to the creation of a list of goals for innovative change in residency education and a draft of a quality improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 8 publications
1
13
0
3
Order By: Relevance
“…They appear in the list of goals for innovation in pediatric residency education in the article that summarizes colloquium III. 12 Colloquium II participants also discussed how residency, as only a portion of a career-long continuum of learning, can help pediatricians close the gap between care that is recommended and care that is actually delivered. 39 Restated, what role does residency have in the formation of habits by which new competencies are acquired and incorporated into daily practice?…”
Section: Colloquium Ii: the Theory And Practice Of Graduate Medical Ementioning
confidence: 99%
See 2 more Smart Citations
“…They appear in the list of goals for innovation in pediatric residency education in the article that summarizes colloquium III. 12 Colloquium II participants also discussed how residency, as only a portion of a career-long continuum of learning, can help pediatricians close the gap between care that is recommended and care that is actually delivered. 39 Restated, what role does residency have in the formation of habits by which new competencies are acquired and incorporated into daily practice?…”
Section: Colloquium Ii: the Theory And Practice Of Graduate Medical Ementioning
confidence: 99%
“…A final draft, slightly modified by subsequent discussions, was a principal product of colloquium III. 12 A second focus of colloquium III was how to promote exploration of innovative solutions across pediatric residency training programs. We learned much from similar projects in internal medicine and family medicine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of recommending general changes in the number of months in a particular setting or the required numbers of continuity clinics for all residency training programs, those participating in the R 3 P Project embraced encouraging diverse innovative approaches to improving education. 3,60 In this endeavor, we can profit from the experiences of internal medicine and family medicine, because both fields are going through a similar methodology to achieve improvements in their residency training programs. [61][62][63][64][65] It is our hope that creative approaches fostered under this process will enhance learning, improve patient and family outcomes, and lead to more efficient, effective pediatric care.…”
mentioning
confidence: 99%
“…With this thinking in mind, R 3 P project members selected 3 high-priority goals for residency programs 15,16 : (1) curricula should be weighted toward career choices; (2) programs should reach out to medical schools and postresidency maintenance of certification to make learning a continuum; and (3) programs should document incorporation of attitudes and habits that close the gap between optimal and current health care outcomes (ie, incorporation of qualities that enhance reliable, safe patient care through practice-based learning and improvement). The project concluded that methods of achieving these goals should be based on data.…”
Section: Innovation In Residency Education and Evolving Pediatric Heamentioning
confidence: 99%